2019
DOI: 10.1029/2019gl082045
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic Observations of the 2018 Mw 7.5 Sulawesi Earthquake and Its Implications for the Kinematics of the Palu Fault

Abstract: The ascending and descending interferometric synthetic aperture radar data are used to investigate the fault rupture and slip model of the 2018 Mw 7.5 Sulawesi, Indonesia, earthquake. The best fitting slip model indicates that this earthquake ruptured not only a segment extending the Palu fault to the north but also a northwestern segment offshore. The slip on the onshore fault is predominant left‐lateral strike slip. The slip on the offshore fault is dominated by normal faulting with a maximum slip of ~6.3 m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 32 publications
4
51
0
3
Order By: Relevance
“…This value was subsequently modified to assess its effect on the calculated ΔCFS. Previous studies reported the 2018 Palu Mw 7.5 earthquake fault parameters using seismic wave, GPS, and INSAR data inversions (Bao et al, 2019;Fang et al, 2019;Socquet et al, 2019;Song et al, 2019;Ulrich et al, 2019;Wang et al, 2019aWang et al, , 2019bCevikbilen et al, 2019;USGS). The employed fault-plane segments, fault geometries, and slip distributions differed due to inversion differences in the modelling techniques and data sets.…”
Section: S2 Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…This value was subsequently modified to assess its effect on the calculated ΔCFS. Previous studies reported the 2018 Palu Mw 7.5 earthquake fault parameters using seismic wave, GPS, and INSAR data inversions (Bao et al, 2019;Fang et al, 2019;Socquet et al, 2019;Song et al, 2019;Ulrich et al, 2019;Wang et al, 2019aWang et al, , 2019bCevikbilen et al, 2019;USGS). The employed fault-plane segments, fault geometries, and slip distributions differed due to inversion differences in the modelling techniques and data sets.…”
Section: S2 Methodologymentioning
confidence: 99%
“…Previous studies have revealed the fault rupture process of the 2018 Palu Mw 7.5 earthquake using seismic wave, GPS, and InSAR data inversions (Bao et al, 2019;Fang et al, 2019;Socquet et al, 2019;Song et al, 2019;Ulrich et al, 2019;Wang et al, 2019aWang et al, , 2019bCevikbilen et al, 2019;USGS). The present study used the fault slip model developed by Song (2019) as it exhibited a geometrical simplicity and comparable slip distribution as compared to the other models (Bao et al, 2019;Socquet et al, 2019;Song et al, 2019;Wang et al, 2019).…”
Section: S1 Historical Earthquakesmentioning
confidence: 99%
See 3 more Smart Citations